Inside Cover: Ultra‐Tuning of the Aperture Size in Stiffened ZIF‐8_Cm Frameworks with Mixed‐Linker Strategy for Enhanced CO2/CH4 Separation (Angew. Chem. Int. Ed. 1/2019). Issue 1 (4th December 2018) - Hou, Qianqian; Wu, Ying; Zhou, Sheng; Wei, Yanying; Caro, Jürgen; Wang, Haihui
Abstract : Suppressing the linker mobility and tuning the aperture size of a MOF membrane is important to achieve promising gas sieving performance. In their communication onpage 327 ff., Y. Wei, J. Caro, H. Wang et al. proposed a double strategy of "stiffening and narrowing" to prepare a roughly 500 nm thin hybrid mixed‐linker ZIF‐7x‐8 membrane with suppressed flexibility and narrowed window aperture through a fast current‐driven synthesis (FCDS). The membrane shows significantly sharpened CO2 /CH4 sieving with a separation factor up to 25.